Tingkat Pendidikan, Persepsi Wajib Pajak Orang Pribadi Dan Kepatuhan Penyampaian Surat Pemberitahuan Pajak Penghasilan Kasus Di Perumahan Puri Serpong 2 Kota Tangerang Selatan - Eko Hadi Siswanto (Institut Teknologi dan Bisnis Ahmad Dahlan Jakarta, 2012)
The purpose of this research is to study it there is positive influence of education level and perception of Personal Tax Payer toward The Submission of Annual Income Tax Report. The research method used is causal, with the unit of analysis Personal Tax Payer. Sampling method used stratified random sampling. The level education, perception of Personal Tax Payer and The Submission of Annual Income Tax Report by using the instruments measured questionnaire with likert scale. Source analysis performed by descriptive analysis and linear regression. The result shows that's positive influence of level education and perceptions of Personal Tax Payer together and partial toward The Submission Annual Income Tax Report with determination coefficient is 34,99%.